2018
DOI: 10.1139/er-2018-0039
|View full text |Cite
|
Sign up to set email alerts
|

Air synthesis review: polycyclic aromatic compounds in the oil sands region

Abstract: This air synthesis review presents the current state of knowledge on the sources, fates, and effects for polycyclic aromatic compounds (PACs) and related chemicals released to air in the oil sands region (OSR) in Alberta, Canada. Through the implementation of the Joint Canada–Alberta Oil Sands Monitoring Program in 2012 a vast amount of new information on PACs has been acquired through directed monitoring and research projects and reported to the scientific community and public. This new knowledge addresses qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 156 publications
1
50
0
Order By: Relevance
“…The Alberta oil sands (OS) is a large unconventional crude oil deposit, which is extracted through both open-pit mining and in-situ steam assisted techniques. Considering the scale of OS oil production, a number of environmental concerns associated with OS air emissions have arisen, including the potential for ecosystem toxicity (Kirk et al, 2014;Harner et al, 2018) and acid deposition (Jung et al, 2011;Makar et al, 2018). Recent field measurements have shown that OS mining and processing facilities are a large source of volatile organic compounds (VOCs) (Simpson et al, 2010;Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Alberta oil sands (OS) is a large unconventional crude oil deposit, which is extracted through both open-pit mining and in-situ steam assisted techniques. Considering the scale of OS oil production, a number of environmental concerns associated with OS air emissions have arisen, including the potential for ecosystem toxicity (Kirk et al, 2014;Harner et al, 2018) and acid deposition (Jung et al, 2011;Makar et al, 2018). Recent field measurements have shown that OS mining and processing facilities are a large source of volatile organic compounds (VOCs) (Simpson et al, 2010;Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The longterm deposition of these toxic pollutants either declined or remained stable with no significant increases detected in these studies. Considerably elevated deposition of non-Hg metals, as well as polycyclic aromatic compounds, occurred within the 50-km radius of oil sand facilities in the Athabasca Oil Sands region (e.g., Kelly et al 2009Kelly et al , 2010Bari et al 2014;Lynam et al 2015;Harner et al 2018). Their deposition in this region likely increased along with rising bitumen production since the mid-1980s (see Statistics Canada 2016).…”
Section: Deposition Of Mercury and Other Toxic Pollutantsmentioning
confidence: 99%
“…Two "integrating themes" were of interest across components: polycyclic aromatic compounds (PACs) and mercury. A summary on PAC integration (Harner et al 2018) is reported in this critical review. The issue of acid deposition was considered in an integrated manner, building upon a long monitoring history in this area (i.e., the Acid Rain Program beginning in the 1970s), and results are highlighted in this critical review (Makar et al 2018).…”
Section: The Scope Of This Critical Reviewmentioning
confidence: 99%
“…The Galarneau et al (2014) study of tailings pond water supported this finding, demonstrating that given known water concentrations, there is a potential for PAHs to partition into the air. Harner et al (2018) also highlighted that potential; in order for the inverse modeling of Parajulee and Wania (2014) to explain the observed ambient concentrations of phenanthrene, pyrene, and benzo[a]pyrene in 2009, their emissions would need to be 2-3 orders of magnitude higher than those reported in the NPRI and APEI databases. More recent emission estimates, also based on inverse modeling, but for a larger amount of ambient monitoring data (Schuster et al 2015), also concluded that PAH emissions are underestimated (Qiu et al 2018).…”
Section: Validation Of Emissions From Aircraft Studiesmentioning
confidence: 99%
See 1 more Smart Citation